2009
DOI: 10.2337/dc08-1956
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability Correlates Strongly With Postprandialβ-Cell Dysfunction in a Segment of Type 2 Diabetic Patients Using Oral Hypoglycemic Agents

Abstract: OBJECTIVEGlucose fluctuations trigger activation of oxidative stress, a main mechanism leading to secondary diabetes complications. We evaluated the relationship between glycemic variability and β-cell dysfunction.RESEARCH DESIGN AND METHODSWe conducted a cross-sectional study in 59 patients with type 2 diabetes (aged 64.2 ± 8.6 years, A1C 6.5 ± 1.0%, and BMI 29.8 ± 3.8 kg/m2[mean ± SD]) using either oral hypoglycemic agents (OHAs) (n = 34) or diet alone (nonusers). As a measure of glycemic variability, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
71
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 25 publications
12
71
0
3
Order By: Relevance
“…In 42 patients with C-peptide-negative T1DM who received intraportal implantation of cultured islet cell grafts, Gillard et al (18) reported that greater functional b-cell mass of the implant (assessed by glucose clamp) was associated with a reduction in glycemic oscillation, as assessed by the CV of fasting glucose. Moreover, in a study of 59 patients with T2DM who underwent continuous glucose monitoring, postprandial b-cell function (measured by a model-based method during a mixed-meal test) was found to be an independent determinant of glycemic variability on multiple linear regression analyses (17). Similarly, poorer b-cell function on OGTT was associated with increased glycemic variability in participants spanning the spectrum of glucose tolerance from normal to prediabetes to T2DM (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 42 patients with C-peptide-negative T1DM who received intraportal implantation of cultured islet cell grafts, Gillard et al (18) reported that greater functional b-cell mass of the implant (assessed by glucose clamp) was associated with a reduction in glycemic oscillation, as assessed by the CV of fasting glucose. Moreover, in a study of 59 patients with T2DM who underwent continuous glucose monitoring, postprandial b-cell function (measured by a model-based method during a mixed-meal test) was found to be an independent determinant of glycemic variability on multiple linear regression analyses (17). Similarly, poorer b-cell function on OGTT was associated with increased glycemic variability in participants spanning the spectrum of glucose tolerance from normal to prediabetes to T2DM (19).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, cross-sectional studies in both T2DM and T1DM have reported an association between poorer b-cell function and increased glucose variability (17)(18)(19). However, it is not known whether improvement of b-cell function can reduce glycemic variability.…”
mentioning
confidence: 99%
“…Not only hyperglycaemia but also glucose oscilations were considered [25][26][27][28] . Rawlings 29 created a user-friendly Continuous Glucose Monitoring User Interface for Diabetes Evaluation (CGM-GUIDE © ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that the effect of treatment strategy on glycemic variability is relatively small [9,10,33,34]. Whether this was due to insufficient control of glycemic variability with current therapy or to other factors affecting GA/HbA1c should be addressed in future prospective studies.…”
Section: Association Between Postprandial Cpr Index Level and Ga/hba1mentioning
confidence: 99%